Respostas

2013-10-17T20:49:19-03:00
2x + y = 7
   x - y = 2
3x = 9
x = 9 : 3
x = 3
Valor de y: 
2 . 3 + y = 7
6 + y = 7
y = 7 - 6
y = 1
Resposta: x = 3, y = 1

b) 5x + y = - 3
  - 5x + 10 y = 80
          11y = 77
          y = 77 : 11
          y = 7
Valor de x:
5x + 7 = - 3
5x = - 3 - 7
5x = - 10
x = - 10 : 5
x = - 2
Resposta: x = - 2, y = 7

c) x + y = 1138
   x - y = - 540
2x = 598
x = 598 : 2
x = 299
Valor de y:
299 + y = 1138
y = 1138 - 299
y = 839
Resposta: x = 299, y = 839

1 5 1
caraca vlw novamente salvou meu dia
Disponha!